Effectiveness Of Human Resource Management In Improving The Quality Of Government Higher EducationBandar Lampung City - Farizi, Al; Patimah, Siti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
People are one of the most important assets in an organization. The effectiveness of human resource management in improving school quality can be measured using several indicators. One is the ability of school leaders to plan, organize, direct and manage school personnel. The purpose of this study is to analyze the effectiveness of human resource management (HR) for improving the quality of schools in SMA Negeri Se Kota Bandar Lampung. This research includes an analysis of the literature examining the role of human resources in educational settings, including teacher influence, performance management, leadership, collaboration, and parental and community involvement. The research method used is a literature study by collecting data from various theoretical sources and relevant references. Research results show that human resources play an important role in improving school quality. Teachers, the most important human resources department, have great influence in providing quality instruction and guiding students. The importance of teacher professional development and skill enhancement is an important aspect in improving the quality of education. In addition, effective performance management and good leadership help create a positive and motivating work environment for school personnel. The cooperation and participation of parents and the community also helps improve the quality of education. There are various problems in personnel management of public high schools across Bandar Lampung city, such as: Addressing these issues through the development of appropriate policies and practices can ameliorate the potential impacts on school quality, such as ineffective recruitment, lack of skills development and low motivation. increase. It is important to be diligent in recruiting and selecting teachers, providing ongoing training, strengthening performance management, and strengthening partnerships with parents and the community.